Responsibilities of Land Deed Drafting Officials (PPAT) for Sale and Purchase Deeds Made Without Checking the Certificate at the Land Office - Saputro, Ahmadianto; Ma'ruf, Umar (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
The purpose of this research is to analyze the legal responsibilities of land deed making officials for sale and purchase deeds made in front of them without checking the certificate at the Semarang Regency Land Office, to analyze the legal consequences of the sale and purchase deeds made by land deed making officials without checking the certificate. This research is sociological juridical legal research, which is supported by empirical research with descriptive research type. The problem approach used is a qualitative approach. The data used is primary and secondary data consisting of primary legal materials, secondary legal materials. Data collection is through interview studies, observations and direct field observations. Data processing is carried out by examining data, selecting data, classifying data and systematizing data. Next, analyzed descriptively and analytically, the problem formulation in this research was analyzed using Legal Certainty Theory, Responsibility Theory, and Agreement Theory. The results of the research and discussion show that the responsibility of the Land Deed Making Official in the Sale and Purchase of land was not checked at the Semarang Regency Land Office resulting in legal defects in the formal and material requirements in the authentic deed which resulted in the deed being null and void. PPAT sanctions for deeds of sale and purchase that are not in accordance with the procedures for making PPAT deeds or are proven to have committed violations in carrying out their duties and positions so that the deeds they make contain legal defects and the consequences of the PPAT can be subject to sanctions in the form of Administrative Sanctions of the relevant PPAT can be subject to sanctions of dishonorable dismissal from his position, and Civil sanctions in which the deed he made is degraded to a private deed, as well as Criminal Sanctions which can be in the form of a criminal act of participating in falsifying a Deed.